Pengaruh North American Free Trade Agreement (NAFTA) terhadap Perekonomian Meksiko - Agasi, Abim Galau (Global and Policy Journal of International Relations, 2013)
ABSTRACTAt 1994, Mexico have a crisis result to domestic political instability and failures of the devaluation policy. Historically, the Mexican economic crisis had begin from 1980. The crisis in 1980 is result of Mexico’s foreign debt that fail to paid. Mexico made several attemps to rise from the economic crisis. One of the efforts is to be a member of NAFTA. To conform with NAFTA, Mexico changed some national policies. NAFTA is a regional institution for the North American that made by the government of the United States, Canada and Mexico. NAFTA implemented on January 1, 1994. NAFTA has three programs of cooperation, there are Free Trade Agreement, Environmental Cooperation and Labor Cooperation. NAFTA has gradually eliminate obstacles on cross-border trade in the region. NAFTA affected on Mexican economic growth because NAFTA has opened opportunity for Mexico to cooperate with the other NAFTA members. The cooperation aims to attract the foreign investment and increase the value of Mexican exports products, mainly agricultural products, so that GNP will growth and the economic growth will reached too.Keywords: Mexico, Economic Crisis, NAFTA, Cooperation, Economic Growth.DOI:https://doi.org/10.33005/jgp.v1i02.1998